A new occurrence of gomesa leinigii (Pabst) M.W. chase & N.H. williams (orchidaceae) and new populations of macradenia paraensis barb.rodr. (orchidaceae) and peperomia psilostachya C.DC. (piperaceae) in São Paulo State, Brazil - Seidinger, Letícia Chedid [UNESP]; Teixeira, Wilton Felipe; Udulutsch, Renata Giassi [UNESP] (My University, 2018)
We present the first record of Gomesa leinigii (Pabst) M.W. Chase & N.H. Williams in São Paulo state, Brazil, previously known only in the state of Paraná, extended its geographical distribution. We also document newly discovered populations of Macradenia paraensis Barb.Rodr. and Peperomia psilostachya C.DC. in São Paulo state, Brazil. Description, comments, conservation status, photographic figures and a distribution map of these species are presented.
Keywords: Epiphytic flora; IUCN Red List categories; Parque Estadual do Morro do Diabo; Seasonal semi-deciduous fores